Historiographical issues related to the writing of contemporary history of Christianity - Duncan, Graham (Verbum et ecclesia, 2007)
Contemporary history is a fluid concept. Its writing implies commitment and self awareness. The former canons of objectivity, subjectivity and progress as they have traditionally been understood are anachro-nistic. Some of our most valued historical sources were, in their own time, products of contemporary history. Consequently, it may be argued that all history is interpretation and that conclusions reached are, at best, provisional. They are determined by the context, vision and values of the historian which can locate him in terms of the subject under research. Sources are also subject to bias. Church History is goal oriented towards the kingdom of God. The material and outcome of Church History and secular history are the same.